Keterbacaan dan Kesepadanan Makna dalam Terjemahan Buku Cerita Anak: Studi Penerapan Metode Literal dan Word-for-Word - Amalia, Siti Nur; Rohali , Rohali; Setiawan, Teguh (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the readability and semantic equivalence in the translation of a bilingualchildren’s book entitled The Amazing Invisible Tiger. The primary focus lies in how meaning from thesource text is transferred into the target language while considering the characteristics of child readers,particularly in terms of sentence structure, word choice, language style, emotional expression, andcultural context. A qualitative descriptive method was employed to analyze the translation data, withspecific categories including sentence length and complexity, lexical familiarity, child – appropriatelanguage style, as well as lexical accuracy, emotional nuance, and cultural adaptation. The findingsindicate that while most of the translations are lexically accurate, several shifts and shortcomingsremain in the expressive style and cultural relevance, which affect readability and reader engagement.Overly literal translations tend to produce rigid and emotionally flat sentences, reducing the story’sappeal for children. Furthermore, the lack of cultural adaptation contributes to narrative dissonancewithin the local context. These findings highlight the importance of a multidimensional approach inchildren’s book translation one that not only emphasizes accuracy but also ensures the languageremains vivid, emotionally engaging, and relatable to children’s linguistic and social experiences. Thisresearch is expected to contribute to children’s translation practices and offer insights into strategies that are more responsive to the psychological needs of young readers.